EVALUATION OF ENZYME REPLACEMENT THERAPY EFFECTIVENESS IN CHILDREN WITH GAUCHER’S DISEASE ACCORDING TO THE INTERNATIONAL STUDIES - O. S. Gundobina; G. B. Movsisyan; L. S. Namazova-Baranova (Педиатрическая фармакология, 2014)
The article presents data on the history of creation of pathogenetic enzyme replacement therapy and its introduction into clinical practice of managing patients with Gaucher’s disease. 2 primary stages are distinguished: beginning of use of enzyme β-D-glycosidase analog obtained from placenta and alglucerase; introduction of recombinant glucocerebrosidase (imiglucerase). The article demonstrates that enzyme replacement therapy is the only efficient method of treating Gaucher’s disease; according to the international studies; it terminates the primary clinical manifestations of the disease, thus improving quality of life of the patients without any marked side effects. Imiglucerase is used at present; it causes hydrolysis of glycolipid glucocerebroside down to glucose and ceramide by the common way of metabolism of membrane lipids. Imiglucerase is indicated for long-term enzyme replacement therapy in patients with confirmed Gaucher’s disease (types 1 and 3).